Magnetic titanium dioxide nanocomposites for surface-enhanced resonance Raman spectroscopic determination and degradation of toxic anilines and phenols - Han, Xiao Xia; Chen, Lei; Kuhlmann, Uwe; Schulz, Claudia; Weidinger, Inez M.; Hildebrandt, Peter (Angewandte Chemie International Edition, 2014)
Mesoporous M-TiO2 NCs, functionalized by PATP, can capture toxic anilines and phenols by azo coupling. Loading these nanodevices with Ag NPs offers the possibility for a sensitive quantitative determination of target compounds by SERRS spectroscopy, which allows multiplex detection because of the specific vibrational fingerprints. Sensitivity and selectivity can be further enhanced by concentrating the hybrid particles by an external magnet and compound-specific binding (anilines versus phenols). The bound toxic compounds can be degraded by TiO2-assisted photocatalysis after removal of the loaded hybrid particles from the sample solution with an external magnet. The degradation process can be enhanced in the presence of plasmonic Ag nanostructures. Magnetic TiO2 nanocomposites (M-TiO2 NCs) are fabricated and functionalized for determination and elimination of toxic anilines and phenols. The compounds, bound to M-TiO2 NCs by azo coupling, may be degraded by TiO2-assisted photocatalysis, making the NCs recyclable. Addition of Ag nanoparticles allows the detection and identification of the azo products by surface-enhanced resonance Raman spectroscopy and accelerates photocatalytic detoxification. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: aniline; magnetic TiO; phenol; photocatalysis; SERRS